Discovery of driver non-coding splice-site-creating mutations in cancer - Song Cao (Nature Portfolio, 2020)
Non-coding cancer driver mutations that induce splicing variants exist, but are largely unexplored. Here, the authors find these non-coding mutations in known pan-cancer driver genes and show that they create new exons and might interact with pre-existing potential splice sites.